Histological Identification of Animal Protein Ingredients - Krishtafovich, Valentina; Krishtafovich, Dmitry; Belkin, Yuri; Gubarev, Roman (Pakistan Journal of Nutrition, 2015)
The results of microstructural research of powdery animal protein additives produced from pork collagen-containing connective tissue and blood plasma are presented. The analyzed samples had similar composition of collagen and elastin animal proteins. Generally, a protein agent based on animal connective tissue fibers only or in combination with granular eosinophilic protein of a different biological origin is taken as a sample. The rate of hydrolytic changes of connective tissue intercellular substance during technological processing of agents was found different. Plant protein and carbohydrate components were not found.